An investigation of the effect of rapid slurry chilling on blown pack spoilage of vacuum‐packaged beef primals. (1st February 2017) - Reid, R.; Fanning, S.; Whyte, P.; Kerry, J.; Bolton, D.
Abstract: The aim of this study was to investigate if rapid slurry chilling would retard or prevent blown pack spoilage (BPS) of vacuum‐packaged beef primals. Beef primals were inoculated with Clostridium estertheticum subspp. estertheticum (DSMZ 8809), C. estertheticum subspp. laramenise (DSMZ 14864) and C. gasigenes (DSMZ 12272), and vacuum‐packaged with and without heat shrinkage (90°C for 3 s). These packs were then subjected to immediate chilling in an ice slurry or using conventional blast chilling systems and stored at 2°C for up to 100 days. The onset and progress of BPS was monitored using the following scale; 0‑no gas bubbles in drip; 1‑gas bubbles in drip; 2‑loss of vacuum; 3‑'blown'; 4‑presence of sufficient gas inside the packs to produce pack distension and 5‑tightly stretched, 'overblown' packs/packs leaking. Rapid slurry chilling (as compared to conventional chilling) did not significantly affect ( P > 0.05) the time to the onset or progress of BPS. It was therefore concluded that rapid chilling of vacuum‐packaged beef primals, using an ice slurry system, may not be used as a control intervention to prevent or retard blown pack spoilage. Significance and Impact of the Study: This study adds to our growing understanding of blown pack spoilage of vacuum‐packaged beef primals and suggests that rapid chilling of vacuum‐packaged beef primals is not a control option for the beef industry. The results suggest that neither eliminating the heat shrinkage step nor rapid chilling of vacuum‐packaged beef retard the time to blown pack spoilage.